NUMERICAL SIMULATION OF THE TERRITORY FLOODING PROCESS - Pshinko, O. M.; Biliaiev, M. M.; Pokutneva, L. V. (Science and Transport Progress, 2008)
A numerical model to calculate the process of ground waters rise has been proposed. The model is based on the 2-D equations of filtration. The results of numerical experiment are presented.